A retrospective prevalence study of Malaria in an aborigine Hospital in Gombak, Selangor, Malaysia - Jamaiah, I.; Rohela, M.; Nissapatorn, V.; Mohamad Azlan, H.; Nor Adli, A.R.; Shahrul Rizan, I.; Anez, A.; Jasmin, B. (2006)
This was a five-year retrospective study (1999-2004) on the prevalence of malaria at the Aborigine Hospital, Gombak, Malaysia. A total of 94 malaria cases was analysed. The highest case reports were for the year 2000, with 32 cases (34), and the lowest was in 2004, with only 1 (1). The majority of cases reported were among the Semai tribe (44), followed by the Temiar tribe (34) and the unspecified tribe (s) (20). Females (53) were more commonly affected than males (47). The majority of cases were within the age group 1-5 years (51). Plasmodium falciparum was the most common species reported in this study, at 57, followed by Plasmodium vivax (38) and 5 mixed infection of P. falciparum and P. vivax. Most patients (27) stayed for more than one month in hospital. Most patients came from Kuala Lipis, Pahang, (78). The most common complication was anemia (38) followed by splenomegaly (18); only 2 had cerebral malaria. All patients were treated with the standard anti-malarial drugs. No deaths were reported in this study.